COVID-19 Pandemic Impact on Respiratory Infectious Diseases in Primary Care Practice in Children - Ravinder Kaur; Steven Schulz; Naoko Fuji; Michael Pichichero (Frontiers Media S.A., 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic led to day care and school closures and children staying home for several months. When they gradually returned, aggressive regulations were implemented in New York State to reduce viral transmission.Method: An ongoing prospective study occurring in the Rochester, NY region, focused on early childhood respiratory infectious diseases, afforded an opportunity to assess the impact of the pandemic on the incidence of these illnesses in a primary care outpatient setting. Physician-diagnosed, medically attended infection visits were assessed in two child cohorts, age 6-36 months old: from March 15 to December 31, 2020 (the pandemic period) compared to the same months in 2019 (prepandemic). Nasopharyngeal colonization by potential otopathogens during healthy/well-child and acute otitis media (AOM) visits was evaluated.Results: One hundred and forty-four children were included in the pandemic cohort and 215 in the prepandemic cohort. The pandemic cohort of children experienced 1.8-fold less frequent infectious disease visits during the pandemic (p < 0.0001). Specifically, visits for AOM were 3.7-fold lower (p < 0.0001), viral upper respiratory infections (URI) 3.8-fold lower (p < 0.0001), croup 27.5-fold lower (p < 0.0001), and bronchiolitis 7.4-fold lower (p = 0.04) than the prepandemic cohort. Streptococcus pneumoniae (p = 0.03), Haemophilus influenzae (p < 0.0001), and Moraxella catarrhalis (p < 0.0001) nasopharyngeal colonization occurred less frequently among children during the pandemic.Conclusion: In primary care pediatric practice, during the first 9 months of the COVID-19 pandemic, significant decreases in the frequency of multiple respiratory infections and nasopharyngeal colonization by potential bacterial respiratory pathogens occurred in children age 6-36 months old.